Notch Signaling in the Bone Marrow Lymphopoietic Niche - Sottoriva, Kilian; Pajcini, Kostandin V. (Frontiers in Immunology, 2021)
Lifelong mammalian hematopoiesis requires continuous generation of mature blood cells that originate from Hematopoietic Stem and Progenitor Cells (HSPCs) situated in the post-natal Bone Marrow (BM). The BM microenvironment is inherently complex and extensive studies have been devoted to identifying the niche that maintains HSPC homeostasis and supports lifelong hematopoietic potential. The Notch signaling pathway is required for the emergence of the definitive Hematopoietic Stem Cell (HSC) during embryonic development, but its role in BM HSC homeostasis is complicated. Recent work has begun to explore novel roles for the Notch signaling pathway among a variety of BM cellular populations which serve as niche cells for specific lineage progenitor populations which impact hematopoietic differentiation. In this review, we will focus on one such niche where recent findings indicate an important role for Notch signaling in the establishment of a T cell primed sub-population of Common Lymphoid Progenitors (CLPs). Given that its activation mechanism relies primarily on cell-to-cell contact, Notch signaling is an ideal means to discover cellular identity and molecular mechanism of a novel BM lymphopoietic niche. We will discuss how new genetic model systems indicate a pre-thymic, BM-specific role for Notch activation in early T cell development and what this means to the paradigm of lymphoid lineage commitment. Lastly, we will examine how leukemic T-cell acute lymphoblastic leukemia (T-ALL) blasts take advantage of Notch and downstream lymphoid signals in the pathological BM niche.